A colon-targeted delivery system of torularhodin encapsulated in electrospinning microspheres, and its co-metabolic regulation mechanism of gut microbiota. (February 2023) - Liu, Chang; Guo, Yahui; Cheng, Yuliang; Qian, He
Abstract: Torularhodin is a carotenoid with various biological activities. Carotenoids reportedly benefit gut health, but the effect of torularhodin on the gut is unclear. Therefore, torularhodin microspheres were prepared by electrospinning technology, and then their colonic targeting was studied by an in vitro intestinal simulation system. The results show that the torularhodin electrospinning nano-microspheres are highly stable in simulated gastric-small intestine digestion, but can be slowly released in the colon, owing to non-Fickian transport. The diversity and species abundance of gut microbiota after co-culture with torularhodin increased. Prevotella, Phascolarctobacterium, Ruminococcaceae UCG, Faecalibacterium, and Lachnospiraceae UCG were significantly more abundant, while Sutterella, Bacteroides, Escherichia, Collinsella and Intestinimonas were less abundant. Predictive functional results of gut microbiota indicated that torularhodin enhanced lysine biosynthesis of gut microbiota and decreased tyrosine metabolism. The metabolomics results also verified that the above pathways are the main metabolic pathways. Finally, the microbiota-host co-metabolic network clarifies that torularhodin can enhance key metabolites, such as l -lysine and l -carnitine in lysine biosynthesis, and inhibit key metabolites such as l -tyrosine and tyramine in tyrosine metabolism. The gut microbiota mainly involved in the positive regulation were Phascolarctobacterium, Prevotella, and Dialister, while the down-regulated microbes were Collinsella and Intestinimonas . This study demonstrates that torularhodin helps maintain the balance of the "host-gut" ecology, providing new applications for carotenoid-based diets to improve gut health. Graphical abstract: Image 1 Highlights: Torularhodin electrospinning microspheres are stable and slowly released in the colon. Torularhodin enhanced lysine biosynthesis and decreased tyrosine metabolism. Co-metabolic network clarifies torularhodin enhanced l -lysine and l -carnitine. Gut microbiota Phascolarctobacterium, Prevotella, and Dialister were upregulated. Torularhodin helps provide new applications for carotenoid-based diets for gut health.